STRATEGI PEMASAN PRODUK PABRIK TAHU DAN TEMPE DIPONDOK PESANTREN AL-MASHDUQIAH - Raudhatul Jannah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2022)
Competition in economic activities is often used to find out how marketing strategies are formed. To build a marketing strategy by a company, a product can be offered to the market to get attention to be bought, used, or consumed, so that it can fulfill wants and needs. In the marketing mix strategy, the first step that must be done is the product strategy. This is very important because what will be sold is the product and consumers will get to know the company through the products that will be offered. Whereas marketing is marketing, marketing strategy is the design, implementation, and control of plans to influence exchanges to achieve organizational goals. Strategy is an organizational tool used to achieve its goals, and therefore, a marketing strategy is needed to achieve success. This research is a type of field research, which is a study by observing a phenomenon in a scientific situation. While in data collection using, observation, interviews, and documentation. The results of this study explain that the Home Industry for Tofu and Tempe Products uses a face-to-face strategy, a cooperative strategy. And the marketing mix which includes product strategy, price, place, promotion. After exposing the marketing of Thu and Tempe products, it is hoped that the stages of product marketing can be active in all places by looking at the conditions of strengths and weaknesses as well as the changing environment, so that they can find out whether the marketing applied is right on target or not. And further improve the development of employee capabilities to convince the public to trust the industry that has been created by Al-Mashduqiah Islam Pesantren, so that its products become better and also famous among the outside community.